Influence of Material Properties on the Fluid-Structure Interaction aspects during Molded Underfill Process - Khor, C.Y.; Ishak, Muhammad Ikman; Rosli, M.U.; Jamalludin, Mohd Riduan; Zakaria, M.S; Yamin, A.F.M.; Abdul Aziz, M.S.; Abdullah, M.Z. (EDP Sciences, 2017)
This paper presents the investigation of the effects of epoxy moulding compound’ (EMC) viscosity on the FSI aspects during moulded underfill process (MUF). Finite volume (FV) code and finite element (FE) code were connected online through the Mesh-based Parallel Code Coupling Interface (MpCCI) method for fluid and structural analysis. The EMC flow behaviour was modelled by Castro-Macosko model, which was written in C language and incorporated into the FV analysis. Real-time predictions on the flow front, chip deformation and stress concentration were solved by FV- and FE-solver. Increase in EMC viscosity raises the deformation and stress imposed on IC and solder bump, which may induce unintended features on the IC structure. The current simulation is expected to provide the better understandings and clear visualization of FSI in the moulded underfill process.